Cryptographic Algorithm Based on Permutation Ciphers - A. Deepshika; J. Kannan; M. Mahalakshmi; K. Kaleeswari (International Journal of Mathematics And its Applications, 2023)
Cryptography is one of the most needed areas for our society as well as the development of research works. So far, many researchers have contributed to developing algorithms for encryption and decryption. This work is also analogous to them. In this paper, using permutation on n symbols and Hill ciphers, we construct an algorithm for encrypting and decrypting a message. Also, examples for n=2,3,4 and are displayed.